Knockout of Mkp-1 exacerbates colitis in Il-10-deficient mice - Matta, Ranyia (American Physiological Society, 2012)
Il-10-deficient mice develop colitis associated with exaggerated Th1/Th17 responses and are a valuable model of inflammatory bowel disease. Mkp-1 is a major negative regulator of MAPKs, and its expression is enhanced by IL-10. To understand the role of Mkp-1 in the regulation of intestinal mucosal immune responses, we studied the effect of Mkp-1 deletion on the pathogenesis of colitis in Il-10(−/−) mice. We found that knockout of Mkp-1 on an Il-10(−/−) background accelerated the development of colitis. Compared with Il-10(−/−) mice, colitis not only appeared earlier but also was more severe in Il-10(−/−)/Mkp-1(−/−) mice. Il-10(−/−) mice exhibited a mild intestinal inflammation in the specific pathogen-free environment, and rectal prolapse rarely appeared before 6 mo of age. In contrast, the majority of Il-10(−/−)/Mkp-1(−/−) mice developed severe colitis rapidly and presented with rectal prolapse after only 2–3 mo. The colon of Il-10(−/−)/Mkp-1(−/−) mice showed diffuse transmural chronic inflammation and mucosal hyperplasia, with significantly more proliferating crypt epithelial cells than those of Il-10(−/−) mice. In addition to the severe colitis, Il-10(−/−)/Mkp-1(−/−) mice also developed conjunctivitis and blepharitis. The colon of Il-10(−/−)/Mkp-1(−/−) mice contained significantly higher levels of proinflammatory cytokines and exhibited greater MAPK activities than did the colon of Il-10(−/−) mice. Splenocytes and lymphocytes from Il-10(−/−)/Mkp-1(−/−) mice produced higher levels of Th1 cytokines ex vivo upon activation than did cells from Il-10(−/−) mice. Our studies support a pivotal role of Mkp-1 as a negative regulator of mucosal immune responses and highlight its protective function against inflammatory bowel disease.